Expression of LRIG1 is associated with good prognosis and human papillomavirus status in oropharyngeal cancer - Lindquist, D (Nature Publishing Group, 2014)
BACKGROUND: The incidence of human papillomavirus (HPV)-associated oropharyngeal cancer has increased rapidly during the past decades. HPV is typically associated with a favourable outcome; however, a need exists for new and more effective prognostic and predictive markers for this disease. Leucine-rich repeats and immunoglobulin-like domains (LRIG)-1 is a tumour suppressor protein that belongs to the LRIG family. LRIG1 expression has prognostic significance in various human cancers, including cervical cancer, where HPV is a key aetiological agent. METHODS: The prognostic value of LRIG1 and LRIG2 immunoreactivity was investigated in tumour specimens from a Swedish cohort of patients with tonsillar and base of tongue oropharyngeal cancers, including 278 patients. RESULTS: LRIG1 immunoreactivity correlated with disease-free survival and overall survival in univariate and multivariate analyses. Notably, patients with HPV-positive tumours with high LRIG1 staining intensity or a high percentage of LRIG1-positive cells showed a very good prognosis. Furthermore, LRIG1 expression correlated with HPV status, whereas LRIG2 expression inversely correlated with HPV status. CONCLUSIONS: Taken together, the results suggest that LRIG1 immunoreactivity could be a clinically important prognostic marker in HPV-associated oropharyngeal cancer.